Longitudinal association between hemoglobin and lung function with insights into the incidence of airflow obstruction: an observational study - Jihoon Kim; Yun Tae Kim; Ah Young Leem; Ji Ye Jung; Young Sam Kim; Youngmok Park (BMC Pulmonary Medicine)
Abstract Background/Aims Evidence regarding the long-term association between hemoglobin (Hb) levels and lung function in individuals from the general population is scarce. This study aimed to determine the longitudinal association between Hb levels and lung function in a community-based population cohort in South Korea. Methods We used linear mixed regression analysis to evaluate the longitudinal associations between Hb levels and lung function parameters, including forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and FEV1/FVC. Additionally, we used a generalized estimating equation to calculate the odds ratio (OR) of airflow obstruction (AO) according to the Hb level. Results Over an 8-year biennial follow-up of 4,468 individuals (median age, 53.9 years; men, 49.0%), we observed that in men, Hb levels were positively associated with lung function (estimated values of FVC: 16.7 mL, FEV1: 15.5 mL, FEV1/FVC: 0.18%; all P < 0.001) and a decreased incidence of AO (OR = 0.83, P < 0.001). In women, Hb levels were positively associated with FVC but not with FEV1 or FEV1/FVC (estimated values of FVC: 4.7 mL, P = 0.045; FEV1: 3.1 mL, P = 0.142; FEV1/FVC: 0.01%, P = 0.838). The incidence of AO was not significantly different among women (OR = 0.93, P = 0.568). In postmenopausal women, higher Hb levels were associated with increased lung function (estimated values of FVC: 11.8 mL, P < 0.001; FEV1: 9.8 mL, P < 0.001; FEV1/FVC: 0.09%, P = 0.052), but the incidence of AO was not statistically significant (OR = 0.82, P = 0.129). Conclusions A decreased Hb level was associated with reduced lung function and an increased incidence of AO in men.